Toward Robust Interpretation of Low‐Temperature Thermochronometers in Magmatic Terranes. (12th October 2018) - Murray, Kendra E.; Braun, Jean; Reiners, Peter W.
Abstract: Many regions central to our understanding of tectonics and landscape evolution are active or ancient magmatic terranes, and robust interpretation of low‐temperature thermochronologic ages in these settings requires careful attention to the drivers of rock heating and cooling, including magmatism. However, we currently lack a quantitative framework for evaluating the potential role of magmatic cooling—that is, post‐magmatic thermal relaxation—in shaping cooling age patterns in regions with a history of intrusive magmatism. Here we use analytical approximations and numerical models to characterize how low‐temperature thermochronometers document cooling inside and around plutons in steadily exhuming environments. Our models predict that the thermal field a pluton intrudes into, specifically the ambient temperatures relative to the closure temperature of a given thermochronometer, is as important as the pluton size and temperature in controlling the pattern and extent of thermochronometer resetting in the country rocks around a pluton. We identify one advective and several conductive timescales that govern the relationship between the crystallization and cooling ages inside a pluton. In synthetic vertical age‐elevation relationships (AERs), resetting next to plutons results in changes in AER slope that could be misinterpreted as past changes in exhumation rate if the history of magmatism is not accounted for. Finally, we find that large midcrustal plutons, such as those emplaced at ~10–15‐km depth, can reset the low‐temperature thermochronometers far above them in the upper crust—a result with considerable consequences for thermochronology in arcs and regions with a history of magmatic activity that may not have a surface expression. Key Points: Intrusive magmatism may produce important first‐order effects on patterns of low‐temperature thermochronometer cooling Analytical approximations and numerical models predict cooling ages in and around crustal plutons in steadily exhuming environments Large plutons emplaced in the middle crust at 10–15‐km depth can reset low‐temperature thermochronometers in the upper crust